USE OF VIRTUAL REALITY AND GAME TECHNOLOGIES IN TEACHING PHYSICAL CULTURE OF SCHOOLCHILDREN - Цвях, О.О.; Молотильнікова, В.; Бичков, О.Ю. (SWorldJournal, 2024)
Reforming education in Ukraine promotes the use of innovative technologies in physical education and sports, which is one of the promising areas of education development. For modern society, the introduction of innovative technologies in